Application of a modified wake oscillator model to vortex-induced vibration of a free-hanging riser subjected to vessel motion. (1st June 2022) - Qu, Yang; Fu, Shixiao; Xu, Yuwang; Huang, Jun
Abstract: A modified wake oscillator model for modelling vortex-induced vibrations (VIVs) of a free-hanging riser subjected to vessel motion is presented. Different from the conventional wake oscillators which have typically utilized in the prediction of steady flow VIVs, the new model can be applied to simulate VIVs introduced by the vessel motion where the flows around the riser are not known in advance. This has been achieved by introducing an equivalent flow based on the relative flow velocity and coupling the wake oscillator with the acceleration of the riser in the lift direction. The modified wake oscillator model is tuned against the experiments of riser VIVs subjected to steady flows and a set of empirical parameters is obtained. The model is then applied to simulate the VIVs of a large-scale free-hanging water intake riser (WIR) subjected to different vessel motions and the simulated results are compared to those of experiments. The comparison shows that the proposed model is able to predict response frequency in good agreement with the experiment, and generates satisfactory prediction with respect to the response amplitude for three test cases out of five that have been studied in the present paper. Highlights: A modified wake oscillator model is proposed for vessel-motion induced VIV. An equivalent flow and acceleration coupling in the lift direction are introduced. The proposed model is able to predict response in good agreement with the experiment.